ANALYSIS OF RISK-BASED ASSET MANAGEMENT PLAN TO INCREASE PERFORMANCE OF WATER LOCAL COMPANY - Monita Mardika Fajar; Dian Masyita; Leni Susanti (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
This study aims to obtain the concept of risk-based asset management planning with consideration of government regulations and international standards of asset management that can improve the performance of Regional Water Company (PDAM) of Aceh Province. This plan consists of asset procurement plans, asset operating plans, asset maintenance plans, and asset deletion plans. Major risks that can occur in asset management planning include the mismanagement of asset needs, debt settlement failure and corporate financial failure, lack of strong local commitment, real loss, apparent loss, environment, lack of optimal planning and the use of operational costs effectively and efficiently, and the lack of subscribers due to the dominance of people who use groundwater that has an impact on the reluctance of people to buy water through PDAM.